(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
It is safe to say that the praxis of literacy teaching in language classroom has been increasingly growing. Hence, to add this flourishing field of research, the present study portrayed the use of technology in promoting students’ literacy. This article delineated the ways students learn literacy by utilizing technology. Specifically, this paperreported the benefits and challenges of designing digital short story trailers as the result of nurturing EFL readers into storytellers.Moreover, critical questions were posed to assist the participants in developing their idea while designing the video trailers.Empirical data were obtained through observation and interview with eleventh undergraduate student teachers who were voluntarily involved in this descriptive study. Based on the data, findings showed that the activities were successfully help students in pitching the given short story by producing two videos as the result of story reading. Besides, the activity built enjoyable learning experience since the learners wereenthusiastic during the lessons. Moreover, the primary challenges uttered by the participants were their English grammar skills and time limitation. Referring to the aforementioned findings, the pedagogical implication of this research is that integrating appropriate technology to design digital short story trailer in order to promote students’ literacy can be an alternative way in conducting reading course in this digital era.